2017
DOI: 10.1016/j.foreco.2017.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Does the presence of large down wood at the time of a forest fire impact soil recovery?

Abstract: Fire may remove or create dead wood aboveground, but it is less clear how high severity burning of soils affects belowground microbial communities and soil processes, and for how long. In this study, we investigated soil fungal and bacterial communities and biogeochemical responses of severely burned "red" soil and less severely burned "black" soil from a burned forest on the eastern slope of the Cascade Range in Oregon. Specifically, we examined the effects of burn severity on soil nutrients and microbial com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 113 publications
2
8
0
Order By: Relevance
“…We found the common fungi in the NWT were comparable to other boreal regions. Pezizomycetes are known to fruit after fire and includes our most common sequence, Calyptrozyma (Fujimura, Smith, Horton, Weber, & Spatafora, 2005;Smith et al, 2017). This was closely related to a sequence of fungus that colonized roots after fires in Alaska (Bent et al, 2011) but this genus is deemed not to be mycorrhizal according to FUNGuild.…”
Section: Discussionmentioning
confidence: 99%
“…We found the common fungi in the NWT were comparable to other boreal regions. Pezizomycetes are known to fruit after fire and includes our most common sequence, Calyptrozyma (Fujimura, Smith, Horton, Weber, & Spatafora, 2005;Smith et al, 2017). This was closely related to a sequence of fungus that colonized roots after fires in Alaska (Bent et al, 2011) but this genus is deemed not to be mycorrhizal according to FUNGuild.…”
Section: Discussionmentioning
confidence: 99%
“…() reported this trend in soil ectomycorrhizal fungi as consequence of the predominance of Ascomycetes after fire, which we also detected when targeting the whole fungal community. Fire‐resistant Ascomycetes show rapid fruiting, stimulated growth and spore germination due to heating (Cairney & Bastias, ; Dix & Webster, ; Reazin, Morris, Smith, Cowan & Jumpponen, ; Smith et al., ), as well as lower sensitivity to dry conditions compared to Basidiomycetes (Rayner & Boddy, ; cited in Nordén, Götmark, Ryberg, Paltto & Allmér, ) making Ascomycetes more competitive under postfire conditions. Such a shift in the competitive hierarchies, together with the competition among postfire fungi (Dix & Webster, ), could explain the increase phylogenetic α diversity in the fungal community.…”
Section: Discussionmentioning
confidence: 99%
“…Forest fires typically have both short-and long-term effects on fungal communities. As a short-term effect, fire causes a reduction in richness Oliver et al, 2015;Reazin et al, 2016) and as a long-term effect, fire also causes a shift in the presence or relative frequencies of fungal species in the forest system Smith et al, 2017). In this study, we also observed the least fungal taxa richness in the recently burned stand.…”
Section: Taxa Richness and Diversitysupporting
confidence: 64%
“…The diversity value in early stage of fire might be due to the typical effects of fire to limit the type and number of fungal species appearing in an area. Thus, only a few fungi establish early in post-fire conditions, appearing adapted to the environment created after fire (Hansen et al, 2013;Reazin et al, 2016;Smith et al, 2017). In the following successional stage, however, the diversity values showed non-significant differences with the unburned stand (Fig.…”
Section: Tablementioning
confidence: 96%